Sunitinib reduces tumor hypoxia and angiogenesis, and radiosensitizes prostate cancer stem‐like cells. Issue 11 (20th April 2015) - Diaz, Roque; Nguewa, Paul A.; Redrado, Miriam; Manrique, Irene; Calvo, Alfonso
<x xml:space="preserve">Abstract</x> INTRODUCTION The need for new treatments for advanced prostate cancer has fostered the experimental use of targeted therapies. Sunitinib is a multi‐tyrosine kinase inhibitor that mainly targets membrane‐bound receptors of cells within the tumor microenvironment, such as endothelial cells and pericytes. However, recent studies suggest a direct effect on tumor cells. In the present study, we have evaluated both direct and indirect effects of Sunitinib in prostate cancer and how this drug regulates hypoxia, using in vitro and in vivo models. METHODS We have used both in vitro (PC‐3, DU145, and LNCaP cells) and in vivo (PC‐3 xenografts) models to study the effect of Sunitinib in prostate cancer. Analysis of hypoxia based on HIF‐1α expression and FMISO uptake was conducted. ALDH activity was used to analyze cancer stem cells (CSC). RESULTS Sunitinib strongly reduced proliferation of PC‐3 and DU‐145 cells in a dose dependent manner, and decreased levels of p‐Akt, p‐Erk1/2, and Id‐1, compared to untreated cells. A 3‐fold reduction in tumor growth was also observed (P < 0.001 with respect to controls). Depletion of Hif‐1α levels in vitro and a decrease in FMISO uptake in vivo showed that Sunitinib inhibits tumor hypoxia. When combined with radiotherapy, this drug enhanced cell death in vitro and in vivo, and significantly decreased CD‐31, PDGFRβ, Hif‐1α, Id1, and PCNA protein levels (whereas apoptosis was increased) in tumors as compared to controls or single‐therapy treated mice. Moreover, Sunitinib reduced the number of ALDH + cancer stem‐like cells and sensitized these cells to radiation‐mediated loss of clonogenicity. DISCUSION Our results support the use of Sunitinib in prostate cancer and shows that both hypoxia and cancer stem cells are involved in the effect elicited by this drug. Combination of Sunitinib with radiotherapy warrants further consideration to reduce prostate cancer burden. Prostate 75: 1137–1149, 2015. © 2015 Wiley Periodicals, Inc.